Complex hypergeometric functions and integrable many-body problems. (23rd September 2022) - Sarkissian, G A; Spiridonov, V P
Abstract: General reduction of the elliptic hypergeometric equation to the level of complex hypergeometric functions is described. The derived equation is generalized to the Hamiltonian eigenvalue problem for new rational integrable N -body systems emerging from particular degenerations of the elliptic Ruijsenaars and van Diejen models.